Bioethics as mental health? the core response on typhoon rai in Southern Leyte, Philippines - Llorca, Shiela Mae G.; Abiera, Allan M.; Gazo, Daisy D.; Astronomo, Shienazile Edilo; Kahambing, Jan Gresil (Penerbit Universiti Kebangsaan Malaysia, 2022)
Super Typhoon Rai recently devastated the Philippines in December of 2021 and consequently disrupted its public and mental health interventions. With glocality standing at the interface between the global and the local, the objective of the study is to gather the core mental health response of those affected by the Typhoon in the province of Southern Leyte. As a methodology, the paper utilized face-to-face and online qualitative investigation from selected key informants in the province’s towns and islands. The paper is significant since it aims to add to the existing discussion from a province not reported in recent literature from disasters. This study preliminarily enables the emergence of glocal emergency bioethics as a link to disaster mental health.